2021
DOI: 10.1002/btm2.10276
|View full text |Cite
|
Sign up to set email alerts
|

Ferrostatin‐1‐loaded liposome for treatment of corneal alkali burn via targeting ferroptosis

Abstract: Alkali burn is a potentially blinding corneal injury. During the progression of alkali burn‐induced injury, overwhelmed oxidative stress in the cornea triggers cell damage, including oxidative changes in cellular macromolecules and lipid peroxidation in membranes, leading to impaired corneal transparency, decreased vision, or even blindness. In this study, we identified that ferroptosis, a type of lipid peroxidation‐dependent cell death, mediated alkali burn‐induced corneal injury. Ferroptosis‐targeting therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 68 publications
(149 reference statements)
0
23
0
Order By: Relevance
“…DR, characterized by ischemic microvascular disease of the retina and retinal neurodegeneration, is a highly specific complication of diabetes with complex multifactorial pathophysiology, which finally leads to visual impairment or blindness (29). Emerging evidence from a series of in vivo and in vitro studies revealed that ferroptosis, a new type of irondependent programmed cell death linking metabolism, disease, immune cells, and targeted therapy, is closely associated with the pathophysiological states of various ocular diseases, such as corneal alkali burn, glaucoma, age-related macular degeneration, and retinitis pigmentosa (6,(30)(31)(32). Furthermore, targeting ferroptosis is a promising treatment for ocular diseases (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…DR, characterized by ischemic microvascular disease of the retina and retinal neurodegeneration, is a highly specific complication of diabetes with complex multifactorial pathophysiology, which finally leads to visual impairment or blindness (29). Emerging evidence from a series of in vivo and in vitro studies revealed that ferroptosis, a new type of irondependent programmed cell death linking metabolism, disease, immune cells, and targeted therapy, is closely associated with the pathophysiological states of various ocular diseases, such as corneal alkali burn, glaucoma, age-related macular degeneration, and retinitis pigmentosa (6,(30)(31)(32). Furthermore, targeting ferroptosis is a promising treatment for ocular diseases (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…Losmapimod (Los) is a safe and well‐tolerated p38 MAPK inhibitor that shows remarkable inhibiting effects in cardiological, pulmonary, and neural clinical experiments. [ 29 , 30 , 31 ] Based on the potency of Tem and Los for resolution of inflammation and our existing expertise in nanocarriers for ocular surface drug delivery, [ 32 , 33 , 34 ] we developed a novel, safe, and highly effective micellar eye drops that mainly consist of the Los‐loaded and Tem‐conjugated cationic polypeptide micelles, MTem/Los, for the superior combat against DED vicious cycle ( Figure 1 a ). The MTem/Los micelles were prepared simply by the self‐assembly of cationic Tem‐conjugated polypeptides with the Los package.…”
Section: Introductionmentioning
confidence: 99%
“…A film-ultrasonic dispersion method was used to prepare captopril loaded CAFs-targeted liposomes (FH-Lip-Cap). , In brief, a mixture of lipids (30 mg) containing phospholipids (A.V.T, PC98T, N01001), cholesterol (A.V.T, O01001), and DSPE-mPEG 2000 (A.V.T, F01008) was dissolved in dichloromethane at a mole ratio of 20:10:1 (10 mL, DCM). Vacuum rotary evaporator was used to dry the DCM solvent and prepare a thin lipid film at a 50 mL flask.…”
Section: Methodsmentioning
confidence: 99%